Lean distribution to minimize waste of time in the stripping process at PT. Pelabuhan Indonesia IV Ambon Branch - Daniel Bunga Paillin; B.J. Camerling; Cristin Nasarany (Journal of Engineering and Applied Technology, 2020)
Stripping process at PT. Port Indonesia IV (Persero) Ambon Branch plays a very important role for expeditions to receive goods from outside its area to meet market needs. However, in the process of distributing containers to stripping blocks, there is a delay in delivery thus it does not reach the target as a result of waste. Based on the data, it is identified that the total lead time of the stripping process is 3,670 minutes which has a non-value-added activity of 3,090 minutes. It is still found delay that causes the waste so that it needs improvement by minimizing the waste. The purpose of this study is to calculate the efficiency of identified wastes and the total activity of the initial time and time after improvement. Data analysis tools used lean distribution conducted by field observations, interviews, questionnaires, and documentation with data processing techniques in the form of big picture mapping, waste identification, value stream analysis tools (VALSAT), process activity mapping, fishbone diagrams, 5W+1H methods, as well as calculating the efficiency of the improvement time. The result of this study showed that there are four wastes of seven wastes identified namely waste of transportation, waste on unnecessary inventory, waste of defects, and waste of waiting time. Waste of waiting time is a critical waste with a percentage of 29.8% based on the results of questionnaires with the causative factors namely careless parking, not paying attention to stock/targets, limited places, indiscipline, and negligence. After the improvement by minimizing waste, the lead time is 1,550 minutes with a total efficiency of activities of 42%.